Helicoverpa zea gut‐associated bacteria indirectly induce defenses in tomato by triggering a salivary elicitor(s). Issue 3 (7th February 2017) - Wang, Jie; Peiffer, Michelle; Hoover, Kelli; Rosa, Cristina; Zeng, Rensen; Felton, Gary W.
Summary: Insect gut‐associated microbes modulating plant defenses have been observed in beetles and piercing‐sucking insects, but the role of caterpillar‐associated bacteria in regulating plant induced defenses has not been adequately examined. We identified bacteria from the regurgitant of field‐collected Helicoverpa zea larvae using 16S ribosomal RNA (rRNA) gene sequencing and matrix‐assisted laser desorption/ionization time of flight (MALDI‐TOF) mass spectrometry. A combination of biochemical, molecular, and confocal electron microscopy methods were used to determine the role of caterpillar‐associated bacteria in mediating defenses in Solanum lycopersicum (tomato). Laboratory‐reared H. zea inoculated with one of the bacteria identified in field‐collected H. zea, Enterobacter ludwigii, induced expression of the tomato defense‐related enzyme polyphenol oxidase and genes regulated by jasmonic acid (JA), whereas the salicylic acid (SA)‐responsive pathogenesis‐related gene was suppressed. Additionally, saliva and its main component glucose oxidase from inoculated caterpillars played an important role in elevating tomato anti‐herbivore defenses. However, there were only low detectable amounts of regurgitant or bacteria on H. zea ‐damaged tomato leaves. Our results suggest that H. zea gut‐associated bacteria indirectly mediate plant–insect interactions by triggering salivary elicitors. These findings provide a proof of concept that introducing gut bacteria to a herbivore may provide a novel approach to pest management through indirect induction of plant resistance.